2017
DOI: 10.1002/2016jd025592
|View full text |Cite
|
Sign up to set email alerts
|

Radiative effects of absorbing aerosols over northeastern India: Observations and model simulations

Abstract: Multiyear measurements of spectral properties of aerosol absorption are examined over four geographically distinct locations of northeastern India. Results indicated significant spatiotemporal variation in aerosol absorption coefficients (σabs) with highest values in winter and lowest in monsoon. The western parts of the region, close to the outflow of Indo‐Gangetic Plains, showed higher values of σabs and black carbon (BC) concentration—mostly associated with fossil fuel combustion. But, the eastern parts sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 125 publications
(194 reference statements)
1
48
1
Order By: Relevance
“…The TOA RF also is positive for all locations except the GHY and JRH, which are the two major urban locations along the BRV. Significant contribution of absorbing aerosols to lower atmospheric warming over different parts of NE region of India has also been reported by Gogoi et al [62]. Pathak et al [63] have reported that atmospheric forcing due to composite aerosols over Imphal (a valley location south of DMD in NE region of India) was 25. .…”
Section: Aerosol Radiative Forcingmentioning
confidence: 83%
“…The TOA RF also is positive for all locations except the GHY and JRH, which are the two major urban locations along the BRV. Significant contribution of absorbing aerosols to lower atmospheric warming over different parts of NE region of India has also been reported by Gogoi et al [62]. Pathak et al [63] have reported that atmospheric forcing due to composite aerosols over Imphal (a valley location south of DMD in NE region of India) was 25. .…”
Section: Aerosol Radiative Forcingmentioning
confidence: 83%
“…Like the other parts of South Asia (Babu et al, ; Moorthy et al, ), a strong seasonality and distinct spatial features of aerosol distribution are present in this region (Figure ). The observed prominent longitudinal gradient in aerosol distribution with higher AOD values in the western part, during all the seasons is attributed to variability of source types and proximity to the western influences through transport (Pathak et al, 2014, ; Gogoi et al, ). As expected AOD 550 decreases with increase in altitude during all the seasons (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies have identified biomass‐burning (BB) as a major source of aerosols in this region, apart from the locally emitted pollutants (e.g. vehicular exhaust, oil/gas fields, coal mines and biofuels emissions, biogenic emissions from forest) (Pathak et al, ; Gogoi et al, ). However, at DAC (Salam et al, ) and AGA/DHB, soil dust is the major contributor to total aerosols apart from the local and transported anthropogenic aerosols.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AOD exhibits an east-west asymmetry within the North-East region with high values in the western locations (Agartala and Shillong) compared to the eastern locations (Dibrugarh and Imphal) because locations in the western North-East Indian region influenced by both natural (sea salt and soil dust) and anthropogenic aerosols produced locally or transported from IGPs and Bangladesh [12] . The western parts of the North-East region, close to the out flow of IGPs, showed higher values of Black Carbon concentration as well as absorption coefficient which are mostly associated with fossil fuel combustion [13] . By using satellite observations, very recently it has been reported that there is a slightly increasing trend in AOD over seven locations in North-East India for the period July 2002 to December 2013 [14] .…”
Section: Introductionmentioning
confidence: 99%